THE EFFECT OF STATE ASSOCIATIONS ON SCHOOL BOARD GOVERNANCE - Bird, LuAnn (My University, 2009)
Historically, boards of education spent their time on budgets, buildings and managing political disputes. Student performance was delegated to the administration. With the creation of district-wide standards, measures, and assessments, school boards are now held accountable for the performance of students. Recent research links board actions to classroom performance. School board members are trained by their state associations. An analysis of the current Alabama Association of School Board's Academy shows that participation in the program does not lead to higher board performance or improved student achievement. The findings suggest the Association's plans to define board behaviors and actions that lead to higher student performance and identify and measure specific learning outcomes to use in updating the training program may be necessary. Since state associations play an important role in providing support to local school boards, more research is needed to identify effective training services.
A Field Project Submitted In Partial Fulfillment of the Requirements For the Degree of Masters of Public Administration
Keywords: Educational leadership; School mamagement and organization; School boards